The Prevalence of Intimate Partner Violence, Associated Risk Factors, and Other Moderating Effects: Findings From the Kenya National Health Demographic Survey - Memiah, Peter (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is not only a fundamental violation of human rights but also a major public health problem. IPV is the most predominant form of violence committed by men against women. Therefore, our study sought to determine the prevalence of IPV and other moderating factors associated with IPV among these women. This study utilized data from the 2014 Kenya Demographic and Health Survey (KDHS), a nationally representative household-based survey that utilizes a two-stage sampling design. Data was weighted and analyzed using Stata 12 for Windows. A total of 3,028 women were interviewed for the analysis. A majority of the women were aged between 20 and 29 years (1,305; 43.1%), with a greater proportion married (2,329; 76.9%) and identified as Protestant (2,181; 72.1%). On adjusted analysis, factors associated with experiencing IPV included women who: were aged between 40 and 49 years belonging to religions other than Catholic, Protestant, or practiced no religion, resided in urban areas, were currently working, had a poor Wealth Index, were not sexually assertive, had one sexual partner other than their husband/spouse, received money, gifts, or favors in return for sex, had no knowledge on HIV, had husbands/partners aged above 50 years, experienced an early sexual debut of less than 18 years and felt that their partners were justified in beating them. Gender-based violence is complex and multifaceted affecting individuals, families, and society at large and should be addressed from different spectrums of intervention. There is a need for interventions that reduce and prevent IPV through empowering women, creating jobs to accumulate wealth, creating a conducive environment within workplaces for those employed, educating women, and empowering school-aged children to avert IPV.